DEEP GEODYNAMICS AND MANTLE PLUMES: THEIR ROLE IN THE FORMATION OF THE CENTRAL ASIAN FOLD BELT - Yarmolyuk V.V.; Kovalenko V.I. (My University, 2003)
The role of geodynamics and mantle plumes in the formation of the Central Asian Fold Belt is discussed. The isotopic geochemical study demonstrates that the mantle plumes were derived from moderately depleted and enriched mantle reservoirs. Participation of these sources in the magma formation is believed to be related to the domination of one cell mantle convection. The paleogeographic reconstruction show that the Northern Asian Mantle Hot Fields is comparable with the modern African-Atlantic hot superplumes.